2016
DOI: 10.1039/c5en00274e
|View full text |Cite
|
Sign up to set email alerts
|

Chronic addition of a common engineered nanomaterial alters biomass, activity and composition of stream biofilm communities

Abstract: We report that chronic addition of a low-concentration of nano-TiO2 to model streams reduced biofilm-associated microbial abundance and activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…Due to their extensive application, TiO 2 NPs are inevitably released into the environment and are recognized as an emerging environmental stressor (Gondikas et al 2014). As a result, the negative impacts of TiO 2 NPs on animal cells (Yu et al 2017), aquatic organisms (Hu et al 2017), bacterial cells (Liu et al 2016), plants (Zahra et al 2017) , and biofilm communities (Binh et al 2016) have been widely recognized and have raised increasing concerns regarding their biosafety and biosecurity in ecosystems.…”
Section: Accepted Manuscript M a mentioning
confidence: 99%
“…Due to their extensive application, TiO 2 NPs are inevitably released into the environment and are recognized as an emerging environmental stressor (Gondikas et al 2014). As a result, the negative impacts of TiO 2 NPs on animal cells (Yu et al 2017), aquatic organisms (Hu et al 2017), bacterial cells (Liu et al 2016), plants (Zahra et al 2017) , and biofilm communities (Binh et al 2016) have been widely recognized and have raised increasing concerns regarding their biosafety and biosecurity in ecosystems.…”
Section: Accepted Manuscript M a mentioning
confidence: 99%
“…Multi-species communities exposed to ENPs may experience important changes in microbial consortium structure with significant evolutions in microbial diversity (Binh et al, 2014(Binh et al, , 2016Echavarri-Bravo et al, 2015;Jomini et al, 2015;Tang et al, 2017;Miao et al, 2018;Zhu et al, 2018aZhu et al, ,b, 2019. These remodeling of microbial consortia can potentially modify the types of metabolisms expressed in these communities and impact the environmental ENPs fate.…”
Section: Cellular Toxicity Response As a Strong Modifier Of Enps Specmentioning
confidence: 99%
“…However, little is known about how nTiO 2 in combination with UV affect microbial biofilms that determined carbon and nutrient cycling in many ecosystems and, thus, form the basis of food webs. Nonetheless, it was shown that biofilm communities associated with hard substrate may shift towards ROS-tolerant species with implications in their biomass, metabolic activity (Binh et al 2016;Wright et al 2018), and the production of extracellular polymeric substances (Kumari et al 2014) under combined exposures to nTiO 2 and UV. Moreover, heterotrophic biofilms, which are often associated with detritus, exhibit an altered enzymatic activity (Schug et al 2014) under a combined exposure to nTiO 2 and UV, which points towards effects on ecosystem-level processes such as leaf litter decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…These biofilms are thus of paramount importance for the integration of energy bound by leaves into stream food webs (Taylor and Chauvet 2014). Given the documented joint impact of nTiO 2 and UV on bacterial community composition (Binh et al 2016) and microbial enzyme activity (Schug et al 2014), an effect in the nutrition of higher trophic levels may be expected as such implications were shown, for instance, for fungicides and antibiotics (Bundschuh et al 2009;Bundschuh et al 2011).…”
Section: Introductionmentioning
confidence: 99%